Frequency and Outcome of Hepatorenal Syndrome in Decompensated Liver Cirrhosis - Ahmed Adnan, Shahid Bilal, Faiqa Mubeen, S. M. Baquar Raza, Ghulam Muhammad Phull, Nasir Jamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatorenal syndrome (HRS) is a severe complication of chronic liver disease characterized by progressive renal failure. Portal hypertension triggers splanchnic vasodilation, reducing effective blood flow, which in turn stimulates nitric oxide release. This vasodilation activates the renin-angiotensin-aldosterone system, leading to marked renal vasoconstriction and impaired kidney filtration, the hallmark of HRS. This study aimed to find out the frequency and outcome of hepatorenal syndrome in decompensated liver cirrhosis. Methods: A descriptive, cross-sectional study was carried out at the department of medicine, Bahawal Victoria hospital, Bahawalpur from 30th May 2021 to 29th November 2021. Sample size of 96 was calculated by using OpenEpi calculator. A pre-formed questionnaire consisting of demographic data, ultrasound findings, laboratory reports and treatment outcome, was used. Laboratory parameters including bilirubin, prothrombin time, serum albumin, serum creatinine and 24-hour urinary protein were measured. The data was entered and analyzed by using the Statistical Package for Social Science (SPSS) version 23. Results: Total of 96 participants were enrolled in the study, out of them 54.4% were from the age range of 20-40 years and majority were male (82.3%) as compared to their counterpart. About 58 (60.4%) participants reported that duration of disease was more than 1 year. Positive history of smoking was found in 57.3% participants while history of alcoholism was noted in 27.1% participants. Out of total 96 participants, the 17 (17.7%) participants were having hepatorenal syndrome. According to the Child-Pugh classification, the frequency of hepatorenal syndrome in Class A, B and C were 3 (2.12%), 8 (8.33%) and 6 (6.25%) respectively. All the participants responded to the treatment, the 29.4% participants were completely recovered, 47.1% were partially recovered while the mortality rate was 23.5%. Conclusion: Current study concluded that the frequency of hepatorenal syndrome was 17.7% in patients of decompensated liver cirrhosis. According to the Child-Pugh classification, majority of HRS cases (8.33%) fall in Class B while the mortality rate was 23.5%. Keywords: Hepatorenal syndrome, Decompensated liver cirrhosis, Child-Pugh classification